Root Induction of Borneo Prima Tangerine (Citrus Reticulata) By In Vitro Method Using Natural Plant Growth Regulator Raja Banana (Musa Paradisiaca Var. Raja) and Synthetic Naphthalene Acetic Acid (NAA) - Muhammadiyah, Muhammadiyah; Sari, Yanti Puspita; Susanto, Dwi (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Borneo prima tangerine (Citrus reticulata) is a plant species from East Kalimantan, which is expected to become one of the leading citrus in the country. The obstacle to developing this citrus is that cultivation is still limited, so efforts are needed to cultivate plants using in vitro techniques. The process of plant multiplication has been done, the next step is rooting. The purpose of this research is to know the type and concentration of plant growth regulators (PGR) that are optimal in stimulating root growth in Borneo prima tangerine plants. This study used a completely randomized design consisting of 9 treatments, namely control (without the addition of PGR), the addition of natural PGR raja banana extract with concentrations of 25; 50; 75; and 100 g/L, synthetic PGR Naphthalene Acetic Acid (NAA) concentrations of 0.5; 1.0; 1.5; and 2.0 mg/L, each treatment with 3 replicates. The results showed the addition of raja banana extract 75 g/L produced the fastest root emergence time of 3.33 days, the addition of NAA 0.5 mg/L produced the highest number of roots, namely 4.67 roots, and plantain extract 50 g/L produced the longest roots, namely 4.50 cm. This means that the addition of raja banana extract gives the best results in inducing root formation.